Historians about a Counter-Revolutionary Conspiracy in Toulon in 1793 - Viktoria Vladimirovna Verchenkova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2024)
The siege and capture of Toulon in 1793 by the troops of the French Republic continues to be of significant interest to historians, representing one of the most pivotal episodes of the Revolutionary Wars of 1792–1802. However, most researchers focused their attention on a comprehensive account of the military operations that led to the capture of the city by the Republicans. Conversely, they have only briefly addressed the circumstances that led to the anti-French coalition’s unopposed capture of the French fleet’s main base in the Mediterranean. Most historians merely alluded to the existence of a royalist conspiracy as the catalyst for the uprising of the townspeople in July 1793 against the local Jacobin authority and the subsequent capitulation of Toulon to the coalition. This interpretation of events was initially posited in the reports of the people’s representatives to the Convention, and subsequently, during the Restoration era, in the writings of eyewitnesses and contemporaries of those events. This was done to ensure the king’s favour to the townspeople. Historians of the Revolution adopted this interpretation and began to portray the Toulon population as fervent supporters of the monarchy in their writings. This concept was dominant for approximately a century until new approaches to the consideration of the Toulon epic emerged. The relentless pursuit of the underlying motives only served to further obfuscate the situation, rendering it increasingly challenging to ascertain the actual causes of these events. Consequently, historians gradually eschewed conspiracy theories in favour of a more nuanced examination of the role played by the inner-city conflict. Additionally, scholars turned their attention to the economic, political, and social factors that contributed to the anti-Jacobin uprising. Nevertheless, there is still no single, generally accepted approach in historiography that adequately explains the causes of the uprising in Toulon and the subsequent surrender of the city to the British.